Pan-Asian adapted ESMO Clinical Practice Guidelines for the management of patients with metastatic oesophageal cancer: a JSMO–ESMO initiative endorsed by CSCO, KSMO, MOS, SSO and TOS - Muro, Kei; Lordick, Florian; Tsushima, Takahiro; Pentheroudakis, George; Baba, Eishi; Lu, Zhihao; Cho, Byoung Chul; Nor, I.M.; Ng, Matthew; Chen, Li Tzong; Kato, Ken; Li, Jin; et al. (Elsevier, 2019)
The most recent version of the European Society for Medical Oncology (ESMO) Clinical Practice Guidelines for the diagnosis, treatment and follow-up of oesophageal cancer was published in 2016, and covered the management and treatment of local/ locoregional disease, limited disease, locally advanced disease and the management of advanced/metastatic disease. At the ESMO Asia Meeting in November 2017 it was decided by both ESMO and the Japanese Society of Medical Oncology (JSMO) to convene a special guidelines meeting immediately after the JSMO Annual Meeting in 2018. The aim was to adapt the ESMO 2016 guidelines to take into account the ethnic differences associated with the treatment of metastatic oesophageal cancer in Asian patients. These guidelines represent the consensus opinions reached by experts in the treatment of patients with metastatic oesophageal cancer representing the oncological societies of Japan (JSMO), China (CSCO), Korea (KSMO), Malaysia (MOS), Singapore (SSO) and Taiwan (TOS). The voting was based on scientific evidence, and was independent of both the current treatment practices and the drug availability and reimbursement situations in the individual participating Asian countries. © The Author(s) 2018. Published by Oxford University Press on behalf of the European Society for Medical Oncology.